Downregulation of decidual SKP2 is associated with human recurrent miscarriage - Shijian Lv; Mei Liu; Lizhen Xu; Cong Zhang (BMC, 2021)
Abstract Background Recurrent miscarriage (RM) is a very frustrating problem for both couples and clinicians. To date, the etiology of RM remains poorly understood. Decidualization plays a critical role in implantation and the maintenance of pregnancy, and its deficiency is closely correlated with RM. The F-box protein S-phase kinase associated protein 2 (SKP2) is a key component of the SCF-type E3 ubiquitin ligase complex, which is critically involved in ErbB family-induced Akt ubiquitination, aerobic glycolysis and tumorigenesis. SKP2 is pivotal for reproduction, and SKP2-deficient mice show impaired ovarian development and reduced fertility. Methods Here, we investigated the expression and function of SKP2 in human decidualization and its relation with RM. A total of 40 decidual samples were collected. Quantitative PCR analysis, western blot analysis and immunohistochemistry analysis were performed to analyze the differential expression of SKP2 between RM and control cells. For in vitro induction of decidualization, both HESCs (human endometrial stromal cells) cell line and primary ESCs (endometrial stromal cells) were used to analyze the effects of SKP2 on decidualization via siRNA transfection. Results Compared to normal pregnant women, the expression of SKP2 was reduced in the decidual tissues from individuals with RM. After in vitro induction of decidualization, knockdown of SKP2 apparently attenuated the decidualization of HESCs and resulted in the downregulation of HOXA10 and FOXM1, which are essential for normal human decidualization. Moreover, our experiments demonstrated that SKP2 silencing reduced the expression of its downstream target GLUT1. Conclusions Our study indicates a functional role of SKP2 in RM: downregulation of SKP2 in RM leads to impaired decidualization and downregulation of GLUT1 and consequently predisposes individuals to RM.